Improving Teacher Performance through Motivation, Leadership and Commitment of Principal - Sufyarma Marsyidin; Anisah (International Conference on Education, Islamic Studies and Social Sciences Research)
This paper aims to describe the effect of motivation, leadership and comitment of the principal to the teacher performance at Junior High School. The research data was obtained by using questionnaire from 65 teachers. The results showed that (1) the teacher's performance was high, (2) The motivation of principal was high enough, (3) The leadership of the principal was enough, (4) The commitment of principal was high enough, (5) The motivation of principal had positive and significant effect to the teacher performance, (6) The leadership of principal had a positive and significant effect to the teacher performance, (7) The commitment of principal had positive and significant effect to the teacher performance, and (8) The motivation, leadership, and commitment of principal simultaneously influenced the teacher performance.